2011
DOI: 10.1007/82_2011_127
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Therapy in Allergy

Abstract: IgE-mediated allergy is an immunological disorder occurring in response to otherwise harmless environmental antigens (i.e., allergens). Development of effective therapeutic or preventive approaches inducing robust tolerance toward allergens remains an unmet goal. Several experimental tolerance approaches have been described. The therapeutic use of regulatory T cells (Tregs) and the establishment of molecular chimerism are two cell-based strategies that are of particular interest. Treg therapy is close to clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 151 publications
1
16
0
Order By: Relevance
“…T- regulatory cells (T regs ) are a small subset of T-lymphocytes with diverse clinical applications in transplantation, allergy, infectious diseases, GVHD, autoimmunity, cancer, among others12345678910. One fundamental problem stymieing their clinical development is their relative paucity: naturally occurring T regs constitute only 1–5% of total CD4+ T cells in blood, and remain largely dormant until activated.…”
mentioning
confidence: 99%
“…T- regulatory cells (T regs ) are a small subset of T-lymphocytes with diverse clinical applications in transplantation, allergy, infectious diseases, GVHD, autoimmunity, cancer, among others12345678910. One fundamental problem stymieing their clinical development is their relative paucity: naturally occurring T regs constitute only 1–5% of total CD4+ T cells in blood, and remain largely dormant until activated.…”
mentioning
confidence: 99%
“…Allergen-expressing stem cells [122][123][124] Engineered T regulatory cells [126] Engineered Th1 cells [128] E. Passive immunization…”
Section: Coupled Allergensmentioning
confidence: 99%
“…Review: Allergen-specific immunotherapy induce tolerance as has been shown in experimental animal models [122][123][124]. Third, viral-like particleor experimental cell-based forms of prophylaxis may be considered [125][126][127][128].…”
mentioning
confidence: 99%
“…Thus, in contrast to models of molecular chimerism described above, in this study microchimeric levels were sufficient to used (Gattringer et al, submitted data) suggesting that allergens of several categories are potential candidates for molecular chimerism. 13 One of the technical limitations in these studies is the transduction efficiency which varies with each ex vivo treatment after retroviral integration. Low transduction efficiency leads to low levels of chimerism after bone marrow transplantation (BMT).…”
Section: Molecular Chimerism In Allergy: Robust Tolerance Toward Allementioning
confidence: 99%